2020
DOI: 10.5194/npg-27-147-2020
|View full text |Cite
|
Sign up to set email alerts
|

Baroclinic and barotropic instabilities in planetary atmospheres: energetics, equilibration and adjustment

Abstract: Abstract. Baroclinic and barotropic instabilities are well known as the mechanisms responsible for the production of the dominant energy-containing eddies in the atmospheres of Earth and several other planets, as well as Earth's oceans. Here we consider insights provided by both linear and nonlinear instability theories into the conditions under which such instabilities may occur, with reference to forced and dissipative flows obtainable in the laboratory, in simplified numerical atmospheric circulation models… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 103 publications
0
8
0
Order By: Relevance
“…f r and f d are computed from the time-resolved model output, but time-averaged diagnostics are presented for simplicity. Time averaging means the effect of transient eddies (potentially arising due to barotropic and/or baroclinic instabilities; Read et al 2020) on the decomposed height fields is not shown in our analysis. However, we would like to stress that the nonlinear balance given by Equation (19) holds locally in time.…”
Section: Application To Simulationsmentioning
confidence: 99%
“…f r and f d are computed from the time-resolved model output, but time-averaged diagnostics are presented for simplicity. Time averaging means the effect of transient eddies (potentially arising due to barotropic and/or baroclinic instabilities; Read et al 2020) on the decomposed height fields is not shown in our analysis. However, we would like to stress that the nonlinear balance given by Equation (19) holds locally in time.…”
Section: Application To Simulationsmentioning
confidence: 99%
“…Andrews (1984) found that Arnol'd-type stability can only occur for zonally symmetric cases. However, Carnevale & Shepherd (1990) and Mu & Wu (2001) provided further extensions to the theorem, although the restrictions are nontrivial (Read et al 2020). Here we only include this analysis as a means to study the stable or unstable behavior of the long-term trends in our simulations.…”
Section: Dynamical Instabilitymentioning
confidence: 99%
“…Pedlosky 1987; Vallis 2006; Read et al. 2020). No attempt is made to review the entire field and the following discussion is focused on a subset of results that pertain directly to the present investigation.…”
Section: Introductionmentioning
confidence: 99%